Pengendalian Persediaan Bahan Baku Menggunakan Metode Economic Order Quantity Pada Umkm Sabana Fried Chicken Tambun - Nur Azizah; Tri Yuli Handayani; Dwi Astuti (CV. ITTC INDONESIA, 2025)
This research aims to analyze raw material inventory control at Sabana Fried Chicken MSMEs in Tambun by applying the Economic Order Quantity (EOQ) method. The excess stock of raw materials that occurs in MSMEs results in waste and potential losses, especially because fried chicken requires fresh raw materials to maintain quality. By using the EOQ method, this research focuses on optimizing the number of orders for raw materials to minimize total inventory costs, reduce order frequency, and increase operational efficiency. The data used in this research is internal sales and inventory data from April to September 2024. The research results show that implementing the EOQ method can reduce inventory costs and help MSMEs manage stock more effectively, thereby increasing profits and business sustainability. This research provides recommendations for MSMEs to apply the EOQ method as a strategy in inventory control to achieve better operational efficiency and effectiveness